BIOMECHANICAL STUDY OF SINGLE ROOTED TEETH RESTORED WITH DOWEL CORS - M. M. Klepach; B.Y. Silenko; T. A. Khmil; M. V. Khrebor; Y. I. Silenko (Ukrainian Medical Stomatological Academy, 2015)
The purpose of the biomechanical study was a comparative analysis of the stress-strain state of the dowel core, dentin of the tooth root, periodontal and bone tissues of the alveolus in the restoration of the first premolars using dowel core, made of zirconium oxide. Materials and methods. Mathematical modeling was carried out using a service modeling and finite element analysis NASTRAN, designed for implementation on a personal computer in a Windows environment. The package, which is built and analyzed considers an elastic three-dimensional models of dental arches on the basis of finite-element procedures, determines the displacement of each node of the finite element with three axes, the normal and shear stresses, and equivalent stresses according to Huber-Mises, which are calculated according to the formula of mechanics of solid deformable body. Teeth with dowel core are located relative to the coordinate axes that the z axis coincides with the longitudinal axis of the tooth, the x-axis in a distal-medial direction (along the tooth row) and the y-axis in the oral-vestibular (in the perpendicular direction of the dentition). As a main evaluation criterion when comparing the stress-strain state of considered mathematical models of the system "dowel core- recovery single rooted tooth - lower jaw" should take the maximum values of equivalent stresses in the dowel core and the dentin of the root part of the tooth recoverable, arising from the action of the calculated values of functional loads , since exceeding these tension can cause destruction of the root of the tooth or core. As additional evaluation criteria appropriate to compare the maximum values of the equivalent stresses in the adjacent to the root portion of the restored tooth in the periodontium, cortical and trabecular layers of the jawbone. As a result of mathematical analysis of a model system "the root of the tooth, dowel core, crown" found that the horizontal component of the functional load and the combined effect of vertical and horizontal components of the load leads to the localization of fields of maximum values of equivalent stresses in the middle third of the pin of the dowel core from the vestibular or oral side, depending on the direction of the horizontal load. In cases where only the vertical component of the maximum load values of the equivalent stresses occur in the zone of junction of the coronal part of the dowel core to pin. The maximum values of the equivalent stresses in the restored tooth and the periodontal and dowel core arise under the combined action of the vertical component of the functional load from the horizontal, directed in the vestibular- lingual direction. The most dangerous area of the root of the tooth from the point of view of localization of maximum values of equivalent stresses is in the area of dentin adjacent to the end portion of the pin. When restoring the coronal portion of premolar using dowel core maximum values of the equivalent stresses in all structural components of the examined bone tissue does not exceed the corresponding values of ultimate strength, the presence and design of the dowel core significantly affect the values of the equivalent stresses in the dentin of the tooth root, and has almost no effect on stresses in the periodontal and bone tissues of the lower jaw; the localization of the fields of maximum values of equivalent stress on the surface of the root portion of the dentin in the tooth a healthy load corresponds to the location and the value of the equivalent stress tooth under load which restores; the most unfavourable loading is the combined effect of the vertical component of the functional load and the horizontal component, targeted in vestibular- lingual direction.